PERAN KOMPETENSI PROFESIONAL GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN EFEKTIVITAS PEMBELAJARAN - Muhammad Iqbal; Zulkhairi Zulkhairi; Budi Budi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
Teacher Training Management at Darul Hikmah Islamic Boarding School Medan. This study aims to determine: (1) Teacher Training Planning, (2) Teacher Training Organizing, (3) Teacher Training Implementation, (4) Teacher Training Supervision. This study uses qualitative research methods, data collected by observation, interviews, and reviewing documents. The findings of this study reveal four findings, namely: 1) Teacher training planning is contained in the vision, mission and goals of the pesantren and in collaboration with the government or other agencies, whether it is held by public or private universities, 2) Organizing teacher training involves several things, namely: discussion methods and training strategies, as well as democratic leadership in terms of encouraging teacher training motivation, 3) The implementation of teacher training is designed by providing opportunities for teachers to follow it and take a psychological approach and also give appreciation and reword for achievements, 4) Supervision of teacher training This is done by calculating the percentage of training activities and holding teacher performance evaluation meetings and implementing the results of the training.